2006
DOI: 10.1002/ana.20751
|View full text |Cite
|
Sign up to set email alerts
|

Association of the PTPN22*R620W polymorphism with autoimmune myasthenia gravis

Abstract: Our genetic findings strengthen the concept that these groups of patients correspond to etiologically distinct disease entities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
2
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(75 citation statements)
references
References 19 publications
4
67
2
2
Order By: Relevance
“…We found suggestive evidence for association at the PTPN22 locus, as previously noted in EOMG (14,15) (Supplementary Table S3). In contrast, there was only marginal evidence for any association signal for TNIP1 (all P values >0.001 within 100 kb flanking this gene or in r 2 > 0.25), the strongest non-HLA signal we observed in EOMG (15).…”
Section: Screening For Association With Lomgsupporting
confidence: 84%
See 2 more Smart Citations
“…We found suggestive evidence for association at the PTPN22 locus, as previously noted in EOMG (14,15) (Supplementary Table S3). In contrast, there was only marginal evidence for any association signal for TNIP1 (all P values >0.001 within 100 kb flanking this gene or in r 2 > 0.25), the strongest non-HLA signal we observed in EOMG (15).…”
Section: Screening For Association With Lomgsupporting
confidence: 84%
“…PTPN22 was reported in several studies in MG (14,15,41), reaching GWAS criteria in EOMG (15). This association is with the same coding SNP, rs2476601, as in EOMG, with similar effect sizes (ORs 1.62-1.71), and in multiple other autoimmune diseases including type 1 diabetes mellitus, rheumatoid arthritis (RA) and systemic lupus erythematosus (42)(43)(44).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Multiple subsequent studies have confirmed the association of this SNP with T1D, with a recent genome wide meta-analysis reporting a p-value of 5.93x10 -80 and an odds ratio (OR) of 1.96 [4]. This variant is associated with multiple autoimmune diseases, including rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), Graves' disease, and myasthenia gravis [5][6][7][8]. The 1858T variant is a missense mutation of the coding region, in which cytosine is replaced by thymidine at position 1858, resulting in a change from an arginine (R) at position 620 of the protein to tryptophan (W).…”
Section: Genetic Studies and Broad Association Of Ptpn22 1858t With Amentioning
confidence: 99%
“…Their presumed low-expression or low-activity genotypes predispose to multiple autoimmune diseases, including type 1 diabetes, [5][6][7][8][9] Graves' disease, 7,8 hypothyroidism, 6,8 systemic lupus erythematosus, 6,10 rheumatoid arthritis, 6,11 and non-thymoma myasthenia gravis (MG). 12 However, the function of PTPN22 in this tolerance failure 13 has become debatable because of the paradoxically stronger inhibition of T-cell activation 14 by the autoimmunity-prone PTPN22 þ 1858T/T ( 620 W) or C/T genotype rather than the protective þ 1858C/C ( 620 R). A previous study on French subjects showed an association of the PTPN22 þ 1858C/T single nucleotide polymorphism with non-thymoma MG without anti-titin antibodies but not with thymoma-associated MG. 12 It has been found that interleukin-2 (IL-2) is expressed in the thymus during T-cell receptor (TCR)-mediated thymocyte apoptosis, and IL-2/IL-2 receptor (IL-2R) signaling is required for intrathymic negative selection of T cells.…”
Section: Introductionmentioning
confidence: 99%